Reading the Good Samaritan (Lk 10: 25–37) through the lenses of introverted intuition and extraverted intuition: Perceiving text differently - Francis, Leslie J. (HTS teologiese studies, 2022)
Working within the sensing, intuition, feeling, thinking (SIFT) approach to biblical hermeneutics, the present study focuses attention on the distinctive voices of introverted intuition and extraverted intuition, by analysing the way in which two small groups, one comprising dominant introverted intuitive types and the other comprising dominant extraverted intuitive types, explored and reflected on the Lucan narrative of the Good Samaritan, a passage rich in material to stimulate the perceiving process. Two distinctive voices emerged from these two groups.Contribution: Situated within the reader perspective approach to biblical hermeneutics, the SIFT method is concerned with identifying the influence of the psychological type of the reader in shaping the interpretation of text. The foundations of the SIFT approach distinguish among the four functions of sensing, intuition, feeling, and thinking. The present study builds on this foundation by developing the nuance of the orientation in which the function is expressed, in this case focusing specifically on the comparison between introverted intuition and extraverted intuition.